Gambaran Tingkat Nyeri Gout Arthitis di UPTD Puskesmas 1 Baturetno Wonogiri - Adhi Yoga Brata Laksana; Sri Hartutik (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Gout arthritis is a disease in which there is excessive accumulation of uric acid in the body. Based on WHO, the prevalence of gouty arthritis in the world is 34.2%. The impact of gouty arthritis pain can be caused in the form of decreased quality of life of sufferers due to pain that greatly interferes with daily activities: Research objectives the description of the pain level of gouty arthritis in UPTD Puskesmas 1 Baturetno Wonogiri. Methods: Descriptive with a quantitative approach. The research subjects were 196 patients with purposive sampling technique totaling 66 patients. Research instrument (NRS) nurmetic rating scale. Results: Characteristics The majority of gouty arthritis pain levels were elderly at 35 respondents (53%), female gender at 37 (56.1%), the majority of the length of suffering ≥ 5 years at 44 (67.7%), the majority of moderate pain levels with a scale of 4-6 at 31 (47%). Conclusion: the description of the pain level of gouty arthritis at UPTD Puskesmas 1 Baturetno is mostly elderly, female gender, long suffering ≥ 5 years, moderate pain level.